2009
DOI: 10.1103/physrevb.79.205322
|View full text |Cite
|
Sign up to set email alerts
|

Efficient wave-function matching approach for quantum transport calculations

Abstract: The wave-function matching ͑WFM͒ technique has recently been developed for the calculation of electronic transport in quantum two-probe systems. In terms of efficiency it is comparable to the widely used Green's function approach. The WFM formalism presented so far requires the evaluation of all the propagating and evanescent bulk modes of the left and right electrodes in order to obtain the correct coupling between device and electrode regions. In this paper we will describe a modified WFM approach that allow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…In such a device, only the atoms facing the gate electrode will be strongly influenced, and this explains why in Ref. 26 we found that the transport in the device was dominated by tunneling even though the nanotube was 110 Å long, and thus longer than the graphene junctions studied in this paper. Thus, to obtain efficient gating of a nanotube, the gate electrode must wrap around the tube.…”
Section: B Transistor Characteristicsmentioning
confidence: 77%
“…In such a device, only the atoms facing the gate electrode will be strongly influenced, and this explains why in Ref. 26 we found that the transport in the device was dominated by tunneling even though the nanotube was 110 Å long, and thus longer than the graphene junctions studied in this paper. Thus, to obtain efficient gating of a nanotube, the gate electrode must wrap around the tube.…”
Section: B Transistor Characteristicsmentioning
confidence: 77%
“…In order to evaluate the transport properties of the device we use the Landauer-Büttiker approach together with the wave function matching method [49,50] which requires a numerical solution of the scattering problem. A low temperature ∼ 0K and a source-drain bias within the linear response regime are assumed.…”
Section: B Conductancementioning
confidence: 99%
“…The calculation of contact self-energies using iterative and direct approaches (as used here) is already well established in literature. [29,[36][37][38] Nonetheless, we will detail the procedure here. Our reasons for this are twofold; (1) our basis, being non-orthogonal, introduces additional complexity that, to our knowledge, has not been previously described for the direct approach, and (2) our numerical approach avoids some numerical errors in calculating the self-energies directly.…”
Section: Contact Self-energiesmentioning
confidence: 99%